2003
DOI: 10.1212/01.wnl.0000046662.03894.c5
|View full text |Cite
|
Sign up to set email alerts
|

Persistent neutralizing antibodies abolish the interferon β bioavailability in MS patients

Abstract: During IFNbeta therapy, the presence of NAb reduced or abolished bioavailability in a relevant percentage of patients. These data could be important for the early detection of patients with MS who are not responsive to IFNbeta therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 38 publications
9
112
0
1
Order By: Relevance
“…The presence of interferon-␤ NAbs reduces the bioavailability of interferon-␤ and the biological response to injections, although the clinical consequences of this have remained controversial. 67 NAb titers have been measured in all major clinical trials of interferon-␤ (TABLE 6). Increasing titers have been correlated with reduced efficacy on relapse rate and MRI endpoints in a number of these and other trials.…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%
“…The presence of interferon-␤ NAbs reduces the bioavailability of interferon-␤ and the biological response to injections, although the clinical consequences of this have remained controversial. 67 NAb titers have been measured in all major clinical trials of interferon-␤ (TABLE 6). Increasing titers have been correlated with reduced efficacy on relapse rate and MRI endpoints in a number of these and other trials.…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%
“…The presence of NAbs is associated with loss of bioavailable IFN-b. 7,8 Anti- IFN-b antibodies are also associated with a loss of clinical efficacy. 9 The neutralizing antibody in multiple sclerosis (MS) patients is enriched for the IgG4 isotype, and neutralizing IgG antibodies as a whole are found at higher titers than in patients with the non-neutralizing antibody.…”
Section: Introductionmentioning
confidence: 99%
“…Many use an arbitrary titer of 20 neutralizing units (NU) per milliliter as the cutoff value for NAb-positivity, although there is evidence that higher titers (e.g., more than 100 or 200 NU/mL) are more likely to have an impact on clinical parameters and biomarkers than lower titers. 29,31,32,41,48,49 Additionally, some patients revert from NAb-positive to NAb-negative status over time. Reversion is more likely with NAb titers of less than 200 NU/mL, although it can happen at titers as high as 3,094 NU/mL.…”
Section: -49mentioning
confidence: 99%
“…In a Danish study of 455 patients, the authors reported that the cumulative probability of reverting to definitely NAb-negative status (i.e., two consecutive NAb-negative titers) in IFN␤-1b (Betaseron) treated patients was 57% after 42 months (CI ϭ 0.43 to 0.71) compared to only 19% (CI ϭ 0.07 to 0.30) in IFN␤-1a (Rebif) treated patients over the same time period. 13 Because most patients who revert to NAb-negative status tend to have titers of 100 NU/mL or less 29,32,38,41,48,49 such a difference might reflect higher NAb-titers to IFN␤-1a compared to IFN␤-1b. 51 …”
Section: Analysis Of the Evidencementioning
confidence: 99%